Risks in strategies for science and technology development - Long, Hoang Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
The designing of strategies for science and technology development (called afterward as S&T strategies) is the drawing out of future perspectives. If the actually achieved results are lower than being expected the designed perspectives they would be called as unexpected failures and, in practice, it is required to avoid this type of failures. Then, the designing works are required to build up strategic scenarios of S&T strategies which would, at the same time, target high objectives and ensure expected realization of actual objectives. In fact, the risks should be taken as natural and largely regular properties of any strategy. In S&T strategies, risks include various types related to opportunities opened in future, competitions for access commonly opened for all the countries, resources mobilized for realization of strategic objectives, process of building of S&T strategies and others. It is necessary to have right awareness of risks in S&T strategies and then to have adequate attitudes to them. Code: 19022601